A Nanomicellar Prodrug Carrier Based on Ibuprofen-Conjugated Polymer for Co-delivery of Doxorubicin - Li, Zuojun; Sun, Jingjing; Huang, Yixian; Liu, Yanhua; Xu, Jieni; Chen, Yichao; Liang, Lei; Li, Jiang; Liao, Qiongfeng; Li, Song; Zhou, Kechao (Frontiers in Pharmacology, 2018)
Ibuprofen (IBU) is a non-steroidal anti-inflammatory drug (NSAID), which is widely used to reduce fever and treat inflammation and acute pain. Recently, its application in cancer treatment is also being explored. In this work, we synthesized a well-defined IBU-based amphiphilic diblock copolymer via reversible addition fragmentation transfer (RAFT) polymerization of IBU-based vinyl monomer. The amphiphilic copolymer POEG-b-PVBIBU (denoted as POVI) was composed of a hydrophilic poly(oligo(ethylene glycol)) block and a hydrophobic IBU-bearing prodrug block, which was able to self-assemble into prodrug nanomicelles. In addition, it could serve as a carrier to co-load other drugs including doxorubicin (DOX), paclitaxel (PTX), and docetaxel (DTX). By using DOX as a model anti-cancer drug, the delivery function of POVI carrier, including the drug release, in vitro cytotoxicity, cellular uptake, and in vivo antitumor activity, was evaluated. DOX-loaded POVI micelles exhibited sustained release of DOX. Besides, DOX/POVI micelles were effectively taken up by tumor cells with an efficiency comparable to that of free DOX. Moreover, in vivo studies showed that POVI carrier itself had modest antitumor activity. After loading DOX, the antitumor activity was significantly increased, which was significantly higher than that of free DOX. Our results suggest that POVI polymer represents a simple and effective dual-functional carrier for co-delivery of IBU and DOX to improve the anticancer activity.